Exploring The Impact of Motivation on Job Performance: A Study of Government Personnel in Public Sector Organizations - Fabre, John Alvin H.; Liban-Benemerito, Dyan Krysza Janine G.; Alejandro, Jonafe I.; Malang, Bernandino P.; Malang, Jocelyn DS. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
The study aims to explore the relationship between motivation and job performance among government personnel in public sector organ-izations. Specifically, it seeks to understand how various motivational factors influence employee productivity and overall performance in the context of public sector work environments. Motivation theories like Maslow's Hierarchy of Needs (1943) which are composed of five levels of human needs for survival, an individual’s lower-level needs must be satisfied before they can address their higher-level needs. In-trinsic motivation engages a person in an activity for self-satisfaction while extrinsic motivation drives a person to function due to rewards or punishment. This allows us to foresee the incoming demotivator for the personnel and how it affects the performance of the agency where they work. The study used a quantitative research design through a Likert scale questionnaire research instrument. Descriptive statistics and Multivariate Analysis of Variance (ANOVA) were applied to ana-lyze the data, acknowledging potential biases from personal beliefs, professional background, and participant interaction to enhance the study's reliability. The survey results indicated a balanced gender dis-tribution among respondents, falling in the 26 to 35 age group, and most were identified as permanent government personnel. The overall sentiment toward intrinsic motivation and recognition in the work-place was positive, suggesting a healthy organizational climate and a need for improved recognition practices. Additionally, significant dif-ferences in job motivation were noted based on age and length of ser-vice, particularly in the areas of career advancement opportunities and job security. Furthermore, the study reveals that career advancement opportunities are the main motivator for government personnel's job performance, with intrinsic motivation recognized as important, while training programs, performance-based bonuses, and team-building activities are effective strategies for enhancing motivation across diverse demographic profiles.